P129 Endoscopy and inflammatory bowel disease: data from a pilot experience to investigate the gap between the current guidelines and the real clinical practice. (25th January 2019) - Mocciaro, F; Magro, B; Conte, E; Bonaccorso, A; Scimeca, D; Di Mitri, R
Abstract: Background: Endoscopy plays an essential role in inflammatory bowel disease (IBD). ECCO promoted specific consensus on the appropriate indication and application of endoscopy in IBD patients. Nevertheless, up to know endoscopy risks being under or overused. We explored whether the use of colonoscopy is appropriate in a real clinical setting. Methods: We collected data from 150 consecutive colonoscopy performed in our unit (referral centre for endoscopy in IBD). In Table 1 we reported the kind of the collected data. Results: We analysed 72 males and 78 females (mean age of 45.4 ± 16.7 years): 49.3% were Crohn's disease (CD) patients and 50.7% ulcerative colitis patients. Table 1 shows patients' characteristics. Fifty-seven per cent of patients preferred a 'low-volume" bowel preparation, especially those with CD ( p = 0.005), an adequate degree ( p < 0.001), and < 40 years-old ( p = 0.01); 28% of all patients chose the 'split' modality (bowel preparation in 2 days) especially those with an adequate degree ( p = 0.05). At the final analysis 84.6% of patients reached an adequate intestinal cleansing: patients with comorbidities presented a greater risk of intestinal cleanliness ( p = 0.04). No difference between low and high volume bowel preparation was observed concerning the adequate intestinal cleansing as well as between split and non-split methods. Fourteen per cent of patients underwent endoscopy with a 'weak' clinical indication and patients followed-up in a non-IBD referral centre were more exposed to this risk ( p = 0.03). Thirty-two per cent of patients with long-standing colonic involvement underwent colonoscopy for dysplasia surveillance: 16 patients out of 48 (33.3%) underwent colonoscopy after 1–2 years from last endoscopy, 18 (37.5%) after 3–4 year and the remaining 14 patients (29.2%) after more the 4 years. Patients followed-up in a non-IBD referral centre were more exposed to risk of late endoscopies ( p = 0.05). Conclusions: This pilot experience shows that, despite the current guidelines, there are some 'gaps' in prescribing endoscopy in IBD patients with a risk of underuse and overuse of colonoscopy also in referral centres. Patients followed-up in referral centres are more likely to have adequate indication for endoscopy. More careful observance of timing for surveillance colonoscopy remains one of the main issue on which to improve.